Effects of Dietary Docosahexaenoic Acid Levels on the Growth, Body Composition, and Health of Liver and Intestine in Juvenile Tiger Puffer (Takifugu rubripes) - Lu Zhang; Chenchen Bian; Ziling Song; Yang Liu; Jiahao Liu; Qiang Ma; Yuliang Wei; Mengqing Liang; Houguo Xu (Animals)
Docosahexaenoic acid (DHA), a long-chain polyunsaturated fatty acid, plays a critical role in animal growth, inflammatory regulation, lipid metabolism, and neurological functions. However, the optimal dietary requirement of DHA for tiger puffer remains unknown. This study systematically investigated the effects of different dietary DHA levels on the growth performance, body composition, hematological parameters and tissue physiology of tiger puffer (average initial body weight 17.78 ± 1.92 g). Six experimental diets with graded DHA concentrations (0.09%, 0.57%, 1.35%, 1.61%, 2.28%, and 3.08% dry matter) were formulated. The feeding experiment was carried out in a seawater flow-through system for eight weeks, with each diet assigned to three replicate tanks. Based on the regression analysis of weight gain and specific growth rate, the maximum values were observed at the dietary DHA level of 1.75% and 1.88%, respectively. Appropriate DHA levels also significantly improved the muscle protein synthesis and lipid metabolism, and strengthened the intestinal morphology. Furthermore, a threshold for efficient DHA deposition in muscle was identified, beyond which excess DHA (3.08%) may be β-oxidized and therefore largely wasted. In conclusion, the optimal dietary DHA level for juvenile tiger puffer should be within the range of 1.75–1.88%.